The role of biotic and abiotic stress factors on sheep welfare: The example of parasites and climatic changes in European countries - Sotiraki S.; Stefanakis A.; Hoste H.; Maurer V.; Butler G.; Leifert C. (Feeding and management strategies to improve livestock productivity, welfare and product quality under climate change, 2013)
Traditional Mediterranean small ruminants’ production systems mostly involve local breeds, which are kept in outdoor conditions with natural ligneous vegetation and cereal stubble, as major dietary components. Biotic stress factors, in particular, gastrointestinal nematodes remain one of the main threats for the health and the welfare in such ‘low input’ production conditions. Gastrointestinal parasites can cause production losses, increased susceptibility to other diseases and/or pests, and even death. Abiotic stress factors (e.g. temperature stress and imbalanced diets) are known to result in significant reductions in yield and product quality and may increase the susceptibility of animals to parasites and other diseases. Predicted changes in climate are expected to increase heat stress incidence, especially in Southern Europe. Abiotic stress is also known to increase the susceptibility of sheep to gastrointestinal parasites. The predicted impacts of climate change include increased heat stress, changes in semi-natural vegetation cover used for grazing, damaged ecosystems, and rising sea levels. The actual effects are predicted to heterogeneous and to differ between regions. Yet, in most cases, the negative effects are expected to outweigh the benefits and disproportionately hurt traditional small ruminant farmers which in many regions are among the poorest population groups, and have the least capacity for adaptation. Climatic changes will reduce grain yields, will impair pasture composition, quality and quantity, will direct affect pathogen prevalence, incidence and severity and thereby influence animal health and productivity and resource (especially feed) use efficiency. Adaptation of livestock to the more variable environmental conditions predicted as a result of climate change should therefore be a primary focus of R&D focused on improving small ruminant management and breeding systems/strategies. A particular focus should be on improving the sustainability and robustness via the utilization of robust, indigenous breeds rational waste utilisation and management, development of more balanced diets and re-integration of (and nutrient cycling between) local small ruminant and crop production systems.
14. International Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2012/06/15-17, Hammamet (Tunisia)